2018
DOI: 10.1007/s11051-018-4225-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA nanostructure-directed assembly of metal nanoparticle superlattices

Abstract: Structural DNA nanotechnology provides unique, well-controlled, versatile, and highly addressable motifs and templates for assembling materials at the nanoscale. These methods to build from the bottom-up using DNA as a construction material are based on programmable and fully predictable Watson-Crick base pairing. Researchers have adopted these techniques to an increasing extent for creating numerous DNA nanostructures for a variety of uses ranging from nanoelectronics to drug-delivery applications. Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 91 publications
0
49
0
Order By: Relevance
“…DNA origami design is nowadays rather user-friendly, 15 and as the programmable DNA origami structures can be produced at reasonable prices, 47 their use in real world applications is becoming more feasible. Our method is straightforward to employ, and in contrast to previously reported DNA origami directed AuNP superlattices, 25 there is no need to functionalize the AuNPs with singlestranded DNA (ssDNA) sequences. The reported method is not limited to the AuNPs or the DNA origami shapes presented in this work.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…DNA origami design is nowadays rather user-friendly, 15 and as the programmable DNA origami structures can be produced at reasonable prices, 47 their use in real world applications is becoming more feasible. Our method is straightforward to employ, and in contrast to previously reported DNA origami directed AuNP superlattices, 25 there is no need to functionalize the AuNPs with singlestranded DNA (ssDNA) sequences. The reported method is not limited to the AuNPs or the DNA origami shapes presented in this work.…”
Section: Discussionmentioning
confidence: 98%
“…22,23 In addition, DNA nanostructures have been used to direct higher-ordered arrangements of DNA-functionalized metal nanoparticles. 24,25 Recently, DNA origami frames have been used to construct also predefined threedimensional (3D) superlattices. [26][27][28] Spatially ordered structures of AuNPs and other metal nanoparticles have unique electronic, magnetic and optical properties, and are therefore of great interest in a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently a rich toolbox for the preparation of plasmonic nanostructures resembling the proposed geometry become available based on the self-assembly. So far it has been utilized in techniques including colloidal lithography [49] and DNA origami used for nanoscale control of docking of chemically synthesized metallic nanoparticles [50]. These techniques can be in principle used for direct structuring the optical fiber-tip probes as well as on substrates followed by a transfer of the prepared structures to a fiber tip by template stripping [51].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the research group of Bathe et al has already shown that their designer wireframe DNA origami shapes may have an imminent biomedical application, as they created various precise multivalent arrangements of a clinically-relevant HIV gp120 immunogen on the virus-like DNA particles to systematically probe their impact on B cell triggering in vitro [94]. We strongly believe that all these versatile structures will find uses not only in biological research but also in assembling novel functional materials [95][96][97][98].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%